Analysis of kinematic graph learning through the ADDIE model using a neuro-educational approach - Escobar Moreno, Fabiola; Romero Vargas, Sofía (IE Revista de Investigación Educativa de la REDIECH, 2022)
Linking learning processes with neuroscience is one of the challenges that educational research must face in the present century, to give university professors the tools to manage students’ knowledge more efficiently, creating stimulating learning experiences. With this objective, a neuro-educational approach proposal was developed and applied to a University level school to increase students’ ability to understand, analyse and interpret graphs. The proposed learning sequence was specifically applied to the topic of kinematics using the ADDIE model with a mixed approach: quantitative quasi-experimental (using the Z-test) and qualitative. Regarding conceptual gain there are no significant differences between the control and experimental groups, however, from the qualitative approach, students who before the proposed didactic sequence had difficulties to express their ideas in writing and presented problems to differentiate the concepts of velocity and acceleration declare that they identify the development of higher order skills.